2018
DOI: 10.1038/s41533-018-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study validating the German version of the Control of Allergic Rhinitis and Asthma Test (CARAT10)

Abstract: The Control of Allergic Rhinitis and Asthma Test (CARAT10), developed by Portuguese experts, is the only questionnaire assessing asthma control under additional consideration of a frequently concurrent allergic rhinitis (AR), providing sub-scores for both diseases. Aims of this study were the translation and validation of its German version. Asthma patients both with and without AR were included at three primary care pulmologists´ practices in Southern Germany. After translation process, patients completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It is thought that this was due to the shorter time determined for retesting compared with these studies. In the study, the CARAT scale has a with two‐factor structure was in line with previous studies and supports the two‐dimensional structure of the CARAT scale that evaluates the upper and lower airways 22,23 . At the same time, the two‐factor solution was simpler, although the eigenvalue was only just <1.0 and the third factor did account for nearly 10% of the variance.…”
Section: Discussionsupporting
confidence: 89%
“…It is thought that this was due to the shorter time determined for retesting compared with these studies. In the study, the CARAT scale has a with two‐factor structure was in line with previous studies and supports the two‐dimensional structure of the CARAT scale that evaluates the upper and lower airways 22,23 . At the same time, the two‐factor solution was simpler, although the eigenvalue was only just <1.0 and the third factor did account for nearly 10% of the variance.…”
Section: Discussionsupporting
confidence: 89%
“…Construct (convergent) validity was assessed in 14 studies (published in 20 reports), 18–22,35–46,48–50 but one of them did not report correlation coefficients nor areas under the ROC curve 45 . For CARAT, 12 studies out of 13 studies (92%) showed ‘sufficient’ evidence for construct validity 18–22,35–40,42–44,46,48–50 . Eight studies assessed the construct validity for the CARAT subscales 18–22,35–39,48–50 and ‘sufficient’ evidence for construct validity was found in 6 (75%) studies for the upper airway subscale, 18,20–22,35,38,48–50 and 7 (87.5%) studies for the lower airway subscale 18,20–22,35–38,48–50 …”
Section: Resultsmentioning
confidence: 99%
“…The original Portuguese version of CARAT was used in 8 studies (11 reports) 17,19,34–39,42,46,47 . There were 2 studies (3 reports) on the Italian, 40,41,45 German and Dutch 18,21,40 versions of CARAT 22,43,44 . The Turkish version was assessed in one study 20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations